Parents’ Perspectives on the Use of Virtual Reality in Pediatric Chronic Pain Management: Qualitative Study - Lindsay Sullivan; Harrison Vriese; Ellie Ferguson; Megan Armstrong; Hannah Williams; Kathleen Lemanek; Sharon Wrona; Lauren Renner; Lindsey Vater; Henry Xiang (Journal of Medical Internet Research)
Abstract BackgroundVirtual reality (VR) technology holds significant potential for chronic pain management in children and adolescents by providing an alternative and complementary approach to traditional methods of alleviating pain and improving quality of life. Parents play an important role in the successful adoption of VR technologies for children, influencing how children accept, use, and benefit from it. However, little is known about parents’ views on integrating VR technology into pediatric and adolescent chronic pain management. ObjectiveThis study aimed to better our understanding of parents’ perspectives regarding the integration of VR technology into pediatric and adolescent chronic pain management—including barriers, facilitators, and recommendations for future VR technologies. MethodsSemistructured interviews were conducted with parents of children with chronic pain between March and November 2024. Key aspects of the discussion centered on the acceptability, barriers, and enablers of integrating VR technology into pediatric and adolescent chronic pain management. Interviews were audio-recorded, transcribed, and analyzed through inductive thematic analysis. ResultsWe conducted 12 interviews. We identified four broad themes from the interview data: (1) views toward integrating VR technology into chronic pain management (perceived benefits, distraction, and redirection); (2) barriers to using VR technology for chronic pain management (accessibility, complexity, discomfort, and symptom exacerbation); (3) facilitators of integrating VR technology into chronic pain management (addressing financial barriers, integrating VR technology into clinical care, establishing evidence of effectiveness and showcasing positive patient experiences); and (4) recommendations for program content and features (relaxation and mindfulness, physical activity, customization, and social connection). ConclusionsOur findings underscore the perceived benefits of integrating VR technology into pediatric and adolescent chronic pain management to enhance physical, social, and mental health and well-being. However, there are several potential challenges that need to be addressed to improve the accessibility of VR technology for use in pediatric and adolescent chronic pain management. Our findings yielded several practical suggestions to guide the development of effective and equitable VR technology for chronic pain management in children and adolescents.